Regional variation and temporal trend of primary biliary cholangitis epidemiology: A systematic review and meta‐analysis - Lv, Tingting; Chen, Sha; Li, Min; Zhang, Dong; Kong, Yuanyuan; Jia, Jidong (Journal of gastroenterology and hepatology, 2021)
Background and Aim We aimed to estimate the worldwide incidence and prevalence, with focus on the geographical differences and temporal trends. Methods Studies on epidemiology of primary biliary cholangitis (PBC) in PubMed, Embase, and Cochrane Library were systematically retrieved from inception to October 2, 2020. Random‐effect model was applied to estimate the pooled PBC incidence and prevalence rates. Subgroup analysis, meta‐regression, and sensitivity analysis were conducted to find out the cause for heterogeneity. Results Out of 3974 records identified through database searching, 47 population‐based studies were finally included. The pooled global incidence and prevalence of PBC were 1.76 and 14.60 per 100 000 persons, respectively. Both the PBC incidence and prevalence were lower in the Asia‐Pacific region (0.84, 9.82 per 100 000 persons) than that in North America (2.75, 21.81 per 100 000 persons) and Europe (1.86, 14.59 per 100 000 persons) (P < 0.05). The incidence and prevalence showed an increasing tendency in all three regions, with the fastest growth of prevalence in North America (P < 0.05). We found a similar incidence and a lower prevalence of PBC in Northern Europe than that in Southern Europe. A higher incidence and prevalence were observed in female individuals and in the elderly (60–79). Conclusion The PBC incidence and prevalence varied widely across regions, with North America being the highest, followed by Europe, and the lowest in the Asia‐Pacific region. Both the incidence and prevalence showed an increasing tendency worldwide, especially in North America.